2p2h effects on the weak pion production cross section - Mariano, Alejandro Edgardo (2015)
The νln → l−p QE reaction on the A-target is used as a signal event or/and to reconstruct the neutrino energy, using two-body kinematics. Competition of another processes could lead to misidentification of the arriving neutrinos, being important the fake events coming from the CC1π background. A precise knowledge of cross sections is a prerequisite in order to make simulations in event generators to substract the fake ones from the QE countings, and in this contribution we analyze the different nuclear effects on the CC1π channel. Our calculations also can be extended for the NC case.